Konflik Pedagang Pasar dan Pemerintah Dalam Kebijakan Relokasi Pasar Tradisional di Kabupaten Ponorogo - Permatasari, Andita Eka (Paradigma, 2022)
This study discusses the conflicts that occur in the management of traditional markets in Ponorogo Regency. Legi Market as one of the largest traditional markets in Ponorogo Regency underwent reconstruction due to a fire that hit in 2017. However, conflicts between traders and the government emerged when the construction of Legi Market was finished. The conflict was triggered by a mismatch in the number of kiosks or stalls and as a result of the implementation of new policies, so a number of traders held demonstrations. The purpose of this study was to determine the dynamics of the conflict between Legi Market traders and the government in the relocation policy of Legi Ponorogo Market and how the government’s role in dealing with these problems. Ralf Dahrendorf’s conflict theory is used to analyze the conflict between traders and the government in the Legi Market relocation policy. Conflict theory views society as a system with different interests in which there are attempts to subdue other elements in order to cover up other interests. This research method is qualitative with the determination of research subjects using purposive techniques. Subjects in the study included the Secretary of the Legislative Ponorogo Market Kiosk Trader Communication Forum (Forkom PKPLP), Pasar Legi general traders, and the Department of Trade, Cooperatives and Micro Enterprises (Perdagkum) of Ponorogo Regency for Market Management. Data collection techniques were carried out by observation and interviews. The results of the study indicate that differences in interests in the relocation policy of Pasar Legi are the main source of conflict between traders and the government. Keywords: Conflict, Traditional Market, Relocation